How lion became king of the animals: and other stories from Africa (Cape Town, South Africa: Tafelberg, 2020)
"Whether they are called creation myths or origin stories, children love these highly imaginative tales of the origins of people, animals and the natural world. This anthology features 14 such tales, with a focus on the animals, people and breathtaking natural beauty of Africa. It includes the San people of Southern Africa's striking story of how the stars and Milky Way were formed, as well as tales explaining how hippopotamus came to live in the water, how Jackal got his black saddle and more."-- Publisher's website.